A rise of state activism in a competitive industry: The case of Russian retail trade law of 2009. Issue 1 (March 2018) - Radaev, Vadim
Abstract: The paper is aimed at exploring the Russian state return to the highly competitive industry of retail trade by adopting restrictive industry-specific legislation in 2009. We reveal a new precedent model of governance using the liberal rhetoric of the competition protection to justify intervention in interfirm contractual relations. We use survey data collected from 843 retailers and suppliers in 2013 to demonstrate that the new legislation had not achieved the proclaimed goals. The paper concludes that instead of market facilitation, the new state activism leads to the further suppression of business and the subversion of antimonopoly policy.